2015
DOI: 10.7860/jcdr/2015/11698.5668
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing Roots: First Case Report of Idiopathic Multiple Cervico–Apical External Root Resorption

Abstract: Idiopathic root resorption is a very rare phenomenon. Resorption in tooth is brought about by odontoclastic activity. Special mechanisms in the periodontal ligament exist to prevent mineralization of the periodontal ligament and these periodontal ligament cells produce factors that inhibit mineralized tissue resorption and are capable of regulating bone and cementum formation. When this mechanism is disturbed it manifests in resorption of root structure. This case report is of a 28-year-old male with a very ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 4 publications
2
19
0
1
Order By: Relevance
“…Various anomalies affecting the hard tissues, including the teeth, are often encountered in regular dental practice (Patil, 2018). Speci ic mechanisms exist in the periodontal region from preventing the mineralization of the periodontal ligament, and the cells of periodontal ligament produce factors that inhibit the resorption of mineralized tissue and control the formation of bone and cementum (Choudhury, 2015). Some studies showed that Uncontrolled type II diabetes was associated with a pronounced increase in the development of dental caries prior to the development of insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Various anomalies affecting the hard tissues, including the teeth, are often encountered in regular dental practice (Patil, 2018). Speci ic mechanisms exist in the periodontal region from preventing the mineralization of the periodontal ligament, and the cells of periodontal ligament produce factors that inhibit the resorption of mineralized tissue and control the formation of bone and cementum (Choudhury, 2015). Some studies showed that Uncontrolled type II diabetes was associated with a pronounced increase in the development of dental caries prior to the development of insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Identi ication of the signs of a possible TMD is essential for diagnosis. Previously our team had conducted numerous case studies (Choudhury and Panigrahi, 2015;Misra et al, 2015) and systematic reviews (Venugopal and Maheswari, 2016;Chaitanya, 2017;Chaitanya et al, 2018;Maheswari et al, 2018) and questionnairebased studies (Subashri and Maheshwari, 2016;Warnakulasuriya and Muthukrishnan, 2018) and international validation study (Steele et al, 2015) and radiographic studies (Rohini and Kumar, 2017;Patil et al, 2018;Subha and Arvind, 2019) over the past 5 years. Now we are focussing on epidemiological surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Smokeless tobacco is also one of the factors for improper oral hygiene (Subashri and Maheshwari, 2016) which leads to many infections such as pericoronitis (Patil et al, 2018), dental caries (Rohini and Kumar, 2017), periodontal problems, tumours not only in the oral cavity, such as hepatocellular carcinoma (Misra et al, 2015). Tobacco chewing indirectly causes root resorption (Choudhury et al, 2015) and osteonecrosis of the jaw (Muthukrishnan et al, 2016). Studies have shown that tobacco interferes with the trigeminal nerve (Holle et al, 2014;Subha and Arvind, 2019).…”
Section: Introductionmentioning
confidence: 99%